Hypo-attenuated leaflet thickening is associated with structural valve deterioration following transcatheter aortic valve replacement. (14th October 2021) - Rashid, H; Ramnarain, J; Nasis, A; Nicholls, S J; Cameron, J D; Gooley, R P
Abstract: Background: While hypo-attenuated leaflet thickening (HALT) has been extensively described following transcatheter aortic valve replacement (TAVR), it remains unclear if HALT impacts long-term prosthetic haemodynamics or predicts structural valve deterioration (SVD). Purpose: To determine the role of HALT and its characteristics of depth and thickness in predicting SVD. Methods: We prospectively evaluated 186 patients who had undergone TAVR with 320-slice CT imaging for the presence of HALT, defined as hypo-attenuation of bioprosthetic leaflets in diastole. All assessments were performed by two blinded operators on the 3Mensio workstation. HALT depth (thickness) was the greatest depth in the sagittal view and HALT area was the greatest area in the axial view. SVD was defined as at least one of mean gradient ≥20 mmHg, increase in gradient ≥10 mmHg from baseline and at least moderate valvular regurgitation. Echocardiograms at discharge, one month and annually were assessed by cardiologists blinded to HALT status. Results: LT prevalence was 17.7% at a median CT scan of 6 weeks. SVD occurred in 8.6% at a median follow-up of 2 years (IQR 1–3); two required valve re-intervention, five required anticoagulation that reversed moderate-severe gradient and nine had mild-moderate gradients that were closely monitored. Patients with HALT were more likely to develop SVD (39.3% vs 1.9%, p<0.01) and higher trans-valvular gradients throughout follow-up at up to 3-year follow-up. HALT affected one leaflet in 17 cases, two leaflets in 13 cases and three leaflets in 3 cases. Patients with HALT had a median cumulative thickness of 2.9 mm (IQR 1.9–4.7) and a median area of 64.2 mm 2 (IQR 40.9–91.6). Threshold for the occurrence of SVD with HALT characteristics were cumulative depth of 2.4 mm (Specificity 94.1%, Sensitivity 75.0%, AUC=0.87) and cumulative area of 28 mm 2 (Specificity 92.2%, Sensitivity 81.3%, AUC=0.86). Conclusion: HALT was associated with SVD and higher trans-valvular gradients following TAVR. HALT depth and area were strong predictors of SVD. CT following TAVR may determine patients at-risk of SVD. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): National Heart Foundation AustraliaNational Health and Medical Research Council Australia